2017
DOI: 10.3989/gya.0818162
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of enhancing the physicochemical and functional characteristics of <em>Nigella sativa</em> oil by using the screw pressing technique for extraction

Abstract: SUMMARY:In the current investigation the crude oil of Nigella sativa was extracted from seeds using hydraulic and screw pressing techniques. Different parameters were evaluated in order to find out the appropriate technique to enhance the physicochemical and functional-related characteristics of the extracted crude oil. Results showed that the acid and peroxide values were significantly lower in the screw pressed oil (SPO) than in the hydraulic pressed oil (HPO). The total phenolic content of the SPO was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
2
7
2
Order By: Relevance
“…This volatile oil contains a major component namely thymoquinone TQ in addition to p-cymene which are considered to be responsible for the protective effect of that volatile oil fraction and its parent crude oil that bears that volatile fraction 13,15 . The content of TQ and p-cymene in the current investigation reached 68.13 and 20.11 , respectively of the total volatile oil composition, as determined by full GC analysis that was illustrated in our recent study 17 .…”
Section: ±008supporting
confidence: 78%
See 3 more Smart Citations
“…This volatile oil contains a major component namely thymoquinone TQ in addition to p-cymene which are considered to be responsible for the protective effect of that volatile oil fraction and its parent crude oil that bears that volatile fraction 13,15 . The content of TQ and p-cymene in the current investigation reached 68.13 and 20.11 , respectively of the total volatile oil composition, as determined by full GC analysis that was illustrated in our recent study 17 .…”
Section: ±008supporting
confidence: 78%
“…Therefore it can be comfortably indicated that the chemical composition of the volatile oil and its content of TQ and p-cymene in the current study is exactly the same as that illustrated before 17 . One should also bear in mind that the other non-volatile components of the whole crude oil of N. sativa like the vitamin E, phytosterols and linolenic acid can also participate beside the volatile oil fraction in the hepato-renal improvement effect of that crude oil due to their anti-inflammatory and/or antioxidant activities 14 .…”
Section: ±008supporting
confidence: 75%
See 2 more Smart Citations
“…Flaxseed oil was extracted from the corresponding seeds by using hydraulic pressing at room temperature as described by Ustun et al [18], and modified by Hamed et al [19]. Briefly, the dry seeds were milled into a fine powder, then batches of the powder, 250 g each, were wrapped in a thick heavyduty cloth and the oil was extracted using an in-house made hydraulic laboratory scale pressing machine manufactured at the National Research Centre, Cairo, Egypt and operated at its maximum pressure (3500 psi) for 1.0 h at room temperature.…”
Section: Extraction Of Flaxseed Oilmentioning
confidence: 99%